Photobiomodulation therapy reduces apoptotic factors and increases glutathione levels in a neuropathic pain model. Issue 9 (December 2016) - Janzadeh, Atousa; Nasirinezhad, Farinaz; Masoumipoor, Masoume; Jameie, Seyed; hayat, Parisa
Abstract Neuropathic pain (NP) is caused by damage to the nervous system due to reactive oxygen spices (ROS) increase, antioxidants reduction, ATP production imbalance, and induction of apoptosis. In this investigation, we applied low-level laser 660 nm (photobiomodulation therapy) as a new strategy to modulate pain. In order to study the effects of photobiomodulation therapy (660 nm) on NP, chronic constriction injury (CCI) model was selected. Low-level laser of 660 nm was used for 2 weeks. Thermal and mechanical hyperalgesia were measured before and after surgery on days 7 and 14, respectively. Paw withdrawal thresholds were also evaluated. Expression of p2x3, Bax, and bcl2 protein was measured by western blotting. The amount of glutathione (GSH) was measured in the spinal cord by continuous spectrophotometric rate determination method. The results are presented as mean ± SD. Statistical analysis of data was carried out using SPSS 21. CCI decreased the pain threshold, 2-week photobiomodulation therapy significantly increased mechanical and thermal threshold, decreased P2X3 expression (p < 0.001), and increased bcl2 expression (p < 0.01), but it was not effective on the Bax expression. We speculated that although photobiomodulation therapy increased ROS generation, it increased antioxidants such as GSH. Increase in bcl2 is another mitochondrial protection mechanism for cell survival and that pain relief and decrease in P2X3 expression confirm it.